Manifestation of the Dostoevsky’s axe in Russian poetry of the XXI century - Poimtsava, Volha A. (Journal of the Belarusian State University. Philology, 2019)
The article researches one of the aspects of the perception of F. M. Dostoevsky in the contemporary Russian poetry. The interpretation of the culturema of an axe is analyzed in details in the texts of I. A. Zhukov, E. A. Katsuba, K. A. Kedrov, B. Sh. Kenzheev, N. L. Kluchareva, L. V. Losev, B. Pankin, K. A. Sapgir. Analysis of twelve works of the mentioned poets shows evidence of the attention to the crisis facts of the XXI century (for example, the dissociation of the consciousness of unconscious, the aggravation of social communication). It is shown that the image of the axe often becomes an independent character, realizing the bloody ideology of radicalism. An attempt to deal with necrophilic views is observed in a parodic derision of the symbol of death through the comedy completion of the composition moves.